Pavement Dweller Center (PDC) – An innovative one-stop service for homeless people: The case of Sajida Foundation's Amrao Manush project. (2nd January 2023) - Rahman, Mashrur; Hasan, Md. Musleh Uddin
ABSTRACT: Pavement dwellers remain largely outside any shelter and social service schemes in developing countries. Most programs for urban poor are settlement specific and primarily targeted to slum communities. A number of initiatives did not succeed in the past mainly because those were limited to providing temporary shelters only. Since homeless is a multidimensional problem, an effective intervention needs to provide multifaceted support to homeless people. This paper presents the case of Amrao Manush project which has developed a model framework to uplift the living condition of homeless people through the Pavement Dweller Centers (PDC) . The PDC offers shelter and multidimensional support to pavement dwellers including day-care facility, child education, basic healthcare service, and skill development training. The project demonstrates how a continuous and stepwise process of upgradation – ranging from providing basic shelter and services to skill development training – can empower homeless people to overcome extreme poverty, find employment opportunities and eventually move out of streets. The paper also discusses the major strengths and weaknesses and suggests potential strategies for further scaling-up the initiative.